Careers after the Armed Forces how to decide on the right career and make a successful transition - Mitchell, Jon (Kogan page, 2009)
This book offers career answers to servicemen and -women leaving the military. Author Jon Mitchell is a job recruiter who specializes in job placement for military veterans. He offers exercises, tools, case studies, and tips designed to ease the transition from active duty to the civilian workforce. The book includes advice on resume preparation, interview techniques, working with job recruiters, and evaluating job offers.